Sistema de gestión de energía dentro de una micro - red aislada basada en un problema de optimización estocástica. - Chasi Cajas, Christian Paúl (2023)
In the last decade, the usage of non-conventional renewable energy (ERNC) such as solar and wind has grown exponentially in order to generate electrical energy in microgrids, the objective is to mitigate 22, reduce the use of fossil fuels, minimize the costs of conventional generation equipment, and supply the demand. In this context, it is necessary to analyze the economic dispatch (ED) as a stochastic optimization problem due to the variability of solar resources, wind energy source was not considered due to low wind speeds. Regarding the energy storage system, Lithium-Ion batteries were used, due to their technical characteristics such as high power, high efficiency, longevity, and safety. The second stage consisted of using the predicted data as input to the MILP optimization problem, where it was found that solar energy contributes 59% to the energy, the surplus allowed the batteries to be charged, and when batteries are in discharge mode, they contribute 25% of the energy, allowing the diesel generator to turn on in short intervals of time, contributing 16% and thus supplying the analyzed demand. Finally, in the third stage, the cost comparison between the stochastic and deterministic approach was performed. In the 24-hour horizon, there were no changes, in the 48-hour horizon, the deterministic was better with a savings of $0.42. However, in the 168h horizon was saved $0.44 by using the stochastic method, concluding that the longer the time horizon, the stochastic approach is going to be better, the operating cost are lower, the diesel generator reduces its mechanical wear. The use of fossil fuel is less and the non-conventional renewable energies is prioritized.